EFFORTS TO IMPROVE MATERNAL PERCEPTION PRETERM INFANTS EXPERIENTIAL LEARNING METHOD HOSPITAL SIDOARJO IN EAST JAVA - Sajidin, Muhammad; Kusmindarti, Indah (JURNAL KEPERAWATAN BINA SEHAT, 2014)
High stress levels of parents , especially mothers , and low levels of competence suggests that parents ( mothers ) still have the right knowledge in the care of preterm infants . This situation affects the level of perception of the mother in the care of preterm infants . The purpose of this research is to improve the mothers perception about the treatment of preterm infants with experientiallearning approach. Methods of achieving goals with Quasy experimental study with pre - post test design . Stages in this study ranging from pre-test data collection through the mother s perception about the care of preterm infants in the treatment group and the control group , the following nursing interventions with experiential learning approach I, II and III , while in the control group according to the procedure deberikan care hospital . Then performed post-test, analysis of test data through a paired t-test and making conclusions, experientiallearning methods to influence maternal perception of preterm infant care. The results of this study are expected to be a guide nurses in the nursing interventions in mothers of preterm infants. Will thus be able to increase the mothers perception of the care of preterm babies so the mother can care for preterm infants in the house correctlyKey words: perception of the mother, preterm infants